2019
DOI: 10.3390/cells8121605
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomes and Other Extracellular Vesicles as New Remedies in the Therapy of Inflammatory Diseases

Abstract: There is growing evidence that mesenchymal stem cell (MSC)-based immunosuppression was mainly attributed to the effects of MSC-derived extracellular vesicles (MSC-EVs). MSC-EVs are enriched with MSC-sourced bioactive molecules (messenger RNA (mRNA), microRNAs (miRNAs), cytokines, chemokines, immunomodulatory factors) that regulate phenotype, function and homing of immune cells. In this review article we emphasized current knowledge regarding molecular mechanisms responsible for the therapeutic effects of MSC-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
442
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 523 publications
(454 citation statements)
references
References 107 publications
(209 reference statements)
11
442
0
1
Order By: Relevance
“…Besides the use of MSC as a transplantable cell system, release of extracellular vesicles (EVs) as cell-free vesicular products, including microvesicles or MSC-derived exosomes, is gaining increased attention for potential clinical applications [ 13 ]. Exosomes represent small particles, approximately 20 to 200nm in diameter, as multivesicular bodies of endocytic origin, released into the extracellular compartment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the use of MSC as a transplantable cell system, release of extracellular vesicles (EVs) as cell-free vesicular products, including microvesicles or MSC-derived exosomes, is gaining increased attention for potential clinical applications [ 13 ]. Exosomes represent small particles, approximately 20 to 200nm in diameter, as multivesicular bodies of endocytic origin, released into the extracellular compartment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the effects were depending on the number of exosomes absorbed by T cells [31]. Also, miRNA had been previously reported to be closely involved in immunosuppression by MSC-EV [14,32]. These experiments demonstrated that MSC-EVs derived miRNA could exert the immunological effects in the therapy.…”
Section: Discussionmentioning
confidence: 91%
“…The immunomodulatory effects of MSCs are not always immunosuppressive as it is depending on inflammatory microenvironments [11][12][13]. The immunoregulatory mechanism of MSCs involves the autocrine or paracrine secretion of factors, chemokines, and exosomes [6,14]. To date, several studies have shown that exosomes can simulate almost all the biological functions of MSCs [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…According to numerous experimental and clinical studies, most MSC-based immunomodulatory functions can be attributed to the immunomodulatory properties of the EVs that they secrete. MSC-EVs are rich in biologically active molecules such as mRNA, miRNA, cytokines, and immune modulators, which regulate the function, phenotype, and viability of immune cells [39]. MSC-EVs with immune regulatory activity are also used to study degenerative, chronic, and infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, miR-let-7b-5b, miR-21-5p, miR-92a-3p, miR-24-3p, and miR-181a-5p bind the most targets related to inflammatory responses. [39]. First, MSC-EVs are easier to manipulate and store [42].…”
Section: Discussionmentioning
confidence: 99%